Polyethylene Glycol Preconditioning: An Effective Strategy to Prevent Liver Ischemia Reperfusion Injury. (15th February 2016) - Bejaoui, Mohamed; Pantazi, Eirini; Calvo, Maria; Folch-Puy, Emma; Serafín, Anna; Pasut, Gianfranco; Panisello, Arnau; Adam, René; Roselló-Catafau, Joan
Abstract : Hepatic ischemia reperfusion injury (IRI) is an inevitable clinical problem for liver surgery. Polyethylene glycols (PEGs) are water soluble nontoxic polymers that have proven their effectiveness in various in vivo and in vitro models of tissue injury. The present study aims to investigate whether the intravenous administration of a high molecular weight PEG of 35 kDa (PEG 35) could be an effective strategy for rat liver preconditioning against IRI. PEG 35 was intravenously administered at 2 and 10 mg/kg to male Sprague Dawley rats. Then, rats were subjected to one hour of partial ischemia (70%) followed by two hours of reperfusion. The results demonstrated that PEG 35 injected intravenously at 10 mg/kg protected efficiently rat liver against the deleterious effects of IRI. This was evidenced by the significant decrease in transaminases levels and the better preservation of mitochondrial membrane polarization. Also, PEG 35 preserved hepatocyte morphology as reflected by an increased F-actin/G-actin ratio and confocal microscopy findings. In addition, PEG 35 protective mechanisms were correlated with the activation of the prosurvival kinase Akt and the cytoprotective factor AMPK and the inhibition of apoptosis. Thus, PEG may become a suitable agent to attempt pharmacological preconditioning against hepatic IRI.